The Nasopalatine Ducts Are Required for Proper Pheromone Signaling in Mice - Levy, Dana Rubi; Sofer, Yizhak; Brumfeld, Vlad; Zilkha, Noga; Kimchi, Tali (Frontiers in Neuroscience, 2020)
The vomeronasal organ (VNO) is specialized in detection of chemosignals, mainly pheromones, which control social communication and reproduction in many mammals. These pheromones must solubilize with nasal fluids before entering the VNO, and it was suggested they are delivered and removed from the VNO by active pumping. Yet, the process by which pheromones are delivered to and cleared from the VNO is unclear. In this study, we first constructed a high-resolution 3D morphological image of the whole adult mouse snout, by using micro-CT with ultra-high-resolution images. We identified a net of micro tunnels starting from the nostrils and extending around and through the VNO. These micro tunnels connect the nasal cavity to the VNO and to the oral cavity via the nasopalatine ducts (NPD). Other micro tunnels connect the nasal cavity to the main olfactory epithelium. We next demonstrated that physical obstruction of the NPD severely impairs the clearance of dissolved compounds from the VNO lumen. Moreover, we found that mice with blocked NPD display alterations in chemosignaling-evoked neuronal activation, in brain regions associated with the vomeronasal system. Finally, NPD-blocked male mice exhibit reduced preference for female chemosignals, and impaired social interaction behavior. Taken together, our findings indicate that the NPD in mice are connected to both the nasal and oral cavity, serving an essential role in regulating the flow of soluble chemosignals through the VNO, and are required for proper pheromone-mediated social communication.